Frank Wigglesworth Clarke diaries - Clarke, Frank Wigglesworth, 1847-1931.
Diaries (30 volumes) containing the greatest details for the early period of Clarke's life, especially the college years.
Physicist, chemist, and geologist.
Collection material in English.
Keywords: Chemists; Geologists; Physicists